Corruption from Fraud Theory Perspective - Efrizal Syofyan (Politeknik Negeri Batam, 2021)
This study aims to analyze the corruption phenomena from a fraud theory perspective. Primarily, we examine the effect of greed, opportunity, need, and Capability on corruption behavior. The sample of this study was 31 corrupt inmates in the Padang II-A prison in Indonesia. The results showed that greed and opportunity affect corruption. But we found that need and Capability did not affect the corruption. This finding implies the body of knowledge that fraud theory may explain the corruption phenomena. This study also has a contribution to the regulators and government.